Intraoperative changes in intraocular temperature during vitrectomy procedures with irrigating solutions differing in temperature - L.I. Anatychuk; N.V. Pasyechnikova; V.A. Naumenko; R.E. Nazaretian; M.M. Umanets; R.R. Kobylianskyi; O.S. Zadorozhnyy (Ukrainian Society of Ophthalmologists, 2019)
Background: Intraoperative intraocular media and irrigation fluid temperature monitoring is not performed during vitreoretinal surgery in current clinical practice. Purpose: To investigate intraoperative changes in intraocular temperature at the major steps of vitreoretinal surgery with irrigating solutions differing in temperature. Materials and Methods: Thirty-nine patients (39 eyes) were under observation before, during and after vitrectomy. Group 1 (20 patients; 20 eyes) and Group 2 (19 patients; 19 eyes) differed with respect to the baseline temperature (24.2 ± 0.52 °С, or 10.3 ± 1.1 °С, respectively) of the irrigating fluid. Room air temperature, irrigating fluid temperature, patient's body temperature, blood pressure, heart rate and blood oxygen saturation, vitreous temperature, and duration of every step of the vitreoretinal procedure were recorded in all cases. Results: Vitrectomy with 24°C or 10°C irrigating solutions resulted in a substantial decrease in temperature in vitreous compartments to the level of moderate or deep hypothermia, respectively. In addition, immediately after vitrectomy, the lowest temperatures were found in the anterior vitreous, and were 30.1 ± 0.45 °С for the 24°C group and 24.37±0.52 °С for the 10°C group. Moreover, after additional surgical manipulations, in the presence of discontinued irrigation, the temperatures in the vitreous compartments were found to gradually increase. Conclusion: Vitreoretinal surgery is performed under conditions of induced uncontrolled local hypothermia, which requires intraoperative monitoring of intraocular temperature and irrigating solution temperature. During a vitroretinal procedure lasting up to 30 minutes, the intraocular contents may be safely cooled to the level of deep hypothermia.